Competition by Choice: The Effect of Consumer Search on Firm Location Decisions - Dudey, Marc (American Economic Review, 1990)
This paper relates firm location choice and consumer search. Firms that cluster together attract consumers by facilitating price comparison, but clustering increases the intensity of local competition. I construct a model which shows that firms may choose head-on competition by locating together. Under reasonable conditions, this is the only equilibrium outcome.